Smart Waste Management System (International Journal of Psychosocial Rehabilitation, 2020)
The technological development has brought about a drastic rise in the volume of excess and discarded goods across both industrial and consumer industries. It adds to the need in and around the cities for stronger waste management schemes. The planned device contains a computer with an ESP8266 microcontroller, an ultrasonically operated sensor, and a GPS camera attached to the trash bins. The ultrasonic sensor tracks the waste level in the cans continuously. When the trash in the can hits a certain point, the ultrasonic sensor and the position of the GPS node are sensed and changed through wireless Internet connectivity in the cloud. Raspberry Pi microcontroller accesses the coordinates from the cloud using Wi-Fi. Top k-query preparation refers to the values for the threshold value consistency of the data sets and then stores those values in the MySQL database table. Planing thus avoids data baseline fragmentation by growing the amount of unknown entries. A website can view the MySQL table positions using PHP code that then displays the positions on a map. It may also be found that the website measures and reveals the shortest path between the points automatically from the experimental tests.